PENINGKATAN RASA INGIN TAHU DAN HASIL BELAJAR MENGGUNAKAN MODEL PjBL PADA MATERI SISTEM PERNAPASAN MANUSIA SISWA KELAS V SD KARITAS NANDAN - Lajar, Maria Oktavia Dera; Purnomo, Puji (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The background to this research is the results of teacher interviews, research observations, and the distribution of questionnaires to fifth-grade students at Karitas Nandan Elementary School. Preliminary data indicated that students' average curiosity was still low, and their learning outcomes on the human respiratory system did not meet the school's learning objective achievement criteria (KKTP), which was 75.00. This study aimed to improve curiosity and learning outcomes for fifth-grade students at Karitas Nandan Elementary School through the application of the Project-Based Learning (PjBL) model to the human respiratory system. This study used Classroom Action Research (CAR). The subjects were fifth-grade students at Karitas Nandan Elementary School in the 2025/2026 academic year. Data collection techniques included observation, questionnaires, interviews, and tests. Data analysis techniques included quantitative and qualitative data analysis. The results showed that the application of the PjBL learning model can improve student curiosity and learning outcomes. The average student curiosity score at baseline was 53.48 (low), increasing to 65.03 (moderate) in cycle I, and then increasing again to 75.51 (high) in cycle II. Meanwhile, the average student learning outcome score at baseline was 69.29, increasing to 74.67 in cycle I, and increasing again to 80.33 in cycle II.